Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1974
DOI: 10.1172/jci107595
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Philadelphia. A hereditary hypodysfibrinogenemia characterized by fibrinogen hypercatabolism.

Abstract: A B STR A CT A new, autosomally inherited abnormal fibrinogen associated with hypofibrinogenemia has been described in several members of a family. Plasma fibrinogen measured either as thrombin-clottable protein or by immunodiffusion revealed a fibrinogen level ranging between 60 and 90 mg/100 ml. The thrombin time of plasma or purified fibrinogen was prolonged and only partially corrected by the addition of calcium. Purified fibrinogen prolonged the thrombin time of normal plasma. Fibrinopeptide release by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 58 publications
1
37
1
Order By: Relevance
“…We found that Fg concentration was greater in spontaneously hypertensive rats (3.7 ± 0.3 mg/ ml) than in age-matched normotensive controls (2.4 ± 0.2 mg/ml) [9]. Fg is synthesized and assembled in hepatocytes and fibroblasts, and when secreted into the circulation, has a plasma half-life that ranges from 3 days to 4 days [12]. Synthesis of Fg involves other inflammatory mediators such as interleukin (IL)-6 and IL-1 [13,14], which like Fg, are associated with elevation of blood pressure [15][16][17] and development of hypertension [15,18,19], respectively.…”
Section: Introductionmentioning
confidence: 80%
“…We found that Fg concentration was greater in spontaneously hypertensive rats (3.7 ± 0.3 mg/ ml) than in age-matched normotensive controls (2.4 ± 0.2 mg/ml) [9]. Fg is synthesized and assembled in hepatocytes and fibroblasts, and when secreted into the circulation, has a plasma half-life that ranges from 3 days to 4 days [12]. Synthesis of Fg involves other inflammatory mediators such as interleukin (IL)-6 and IL-1 [13,14], which like Fg, are associated with elevation of blood pressure [15][16][17] and development of hypertension [15,18,19], respectively.…”
Section: Introductionmentioning
confidence: 80%
“…Vitronectin was prepared and radiolabeled as described above. vWf, fibrinogen, and fibronectin were isolated as described previously (7,56,57 temperature for 2 h. These concentrations of adhesive proteins gave the maximal binding of platelets in dose-response isotherms. After incubation, the solutions were aspirated, and the wells were filled with TBS containing 1% (wt/vol) bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…However, the structure of the abnormal fibrin polymer may well be different from normal, as evidenced by the divergence in solution turbidity at later time points (Fig. 4) Congenital hypodysfibrinogenemia has been described in six families in addition to that reported here (44)(45)(46)(47)(48)(49). Fibrinogen Bethesda II (44), which manifests a slight delay in total fibrinopeptide release, also exhibits a major delay in fibrin monomer polymerization and is therefore dissimilar to fibrinogen Baltimore II.…”
Section: Discussionmentioning
confidence: 76%
“…Fibrinogen Bethesda II (44), which manifests a slight delay in total fibrinopeptide release, also exhibits a major delay in fibrin monomer polymerization and is therefore dissimilar to fibrinogen Baltimore II. The remaining proteins (45)(46)(47)(48)(49) are delayed only in the polymerization phase of coagulation. Thus, fibrinogen Baltimore II is readily distinguished from the other hypodysfibrinogens on the basis of its functional defect, a delay in fibrinopeptide B release.…”
Section: Discussionmentioning
confidence: 99%